Pengaruh Pembelajaran Diferensiasi dalam Pembelajaran Penjas Materi Bahaya Pergaulan Bebas - Tiffani, Radela Ryan; Julianti, Rekha Ratri; Hidayat, Abdul Salam (MAN Insan Cendekia Jambi, 2025)
This study aims to analyze the impact of implementing differentiated instruction on students' learning outcomes in Physical Education, Sports, and Health (PJOK), specifically on the topic of the dangers of risky social behavior. The background of this research is based on the importance of an instructional approach that aligns with students’ needs, interests, and readiness levels. The topic of risky social behavior emphasizes the development of values, attitudes, and decision-making skills, making differentiated instruction a relevant approach to create more meaningful learning experiences. This research employed a quantitative method with a one-group pretest-posttest design. The participants were students of class VIII B at SMPN 1 Jatiluhur. Data were collected through objective tests, observation, and documentation. The data were analyzed using descriptive statistics and a paired sample t-test assisted by SPSS software. The findings showed an increase in the average score from 72.78 (pretest) to 82.46 (posttest). The t-test results indicated a significance value of < 0.001, demonstrating a highly significant effect. Therefore, differentiated instruction proved to be effective in enhancing students' learning outcomes.